The role of the Internet in marketing tourism at travel and tourism agencies in Aden governorate from the point of view of tourist employees - Awad Ahmed Mahfoud, Ibtihel (Finance and Business Economies Review, 2019)
The objective of this study is to define the role of the Internet in marketing tourism services at travel and tourism agencies by identifying the point of view of the study sample members regarding the marketing tourism (service, price, promotion, distribution, individuals, physical environment, service delivery) using the Internet. To achieve the study objectives, the researcher chose the analytical descriptive method. The researcher also prepared a survey tool to collect data from the study sample, who were selected using a comprehensive intentional method. Such sample comprised 39 workers employed by travel and tourism agencies in Aden governorate. SPSS was also used for data processing and analysis of sample members responses. The study concluded that the use of the Internet contributes significantly to marketing of tourism service provided by travel and tourism agencies in Aden. In light of the findings of the study, a number of recommendations have been made. The most important of these recommendations are: Taking advantage of technological developments to expand marketing of tourist services, providing electronic software and systems to protect customers, improving agencies’ material environment and creating websites for agencies and banks as a means to improve tourism service marketing.